Student's works classix studio semester 07: Transport-Oriented Vertical Village / Mitchell Tony Mos - Mos, Mitchell Tony (Perpustakaan Tun Abdul Razak, UiTM Sarawak, 2024)
The theme for the project was Transport-Oriented Vertical Village, a multi-storey housing project that will relate to Autonomous Rapid Transit (ART) station that has been envisioned to be backboned of a modern and green public transport system for greater Kuching. The site was located at Jalan Datuk Merican Salleh, Kuching Sarawak surrounded by commercial, residential, hotels, government buildings, schools, clinics and mix-used development. The site was adjacent to the proposed ART station which will provide an interesting setting and context for a transit-oriented residential project. The students are required to conduct a group work to study Transit-Oriented Development and Housing Typology as an obejctive to introduce them to design a high rise building based on local and oversea buildings. Site analysis was conducted along with the conceptual masterplan with requirement provided. The final phase requires student to develop detail design of vertical housing scheme based on the requirement and design aspect that have been studied and researched.